ChemInform Abstract: Ruthenium‐Catalyzed ortho‐C—H Mono‐ and Di‐Imidation of Arenes with N‐Tosyloxyphthalimide. Issue 34 (August 2015) - Yadav, M. Ramu; Shankar, Majji; Ramesh, E.; Ghosh, Koushik; Sahoo, Akhila K.
Abstract An effective imidation of aromatic acid derivatives is achieved by utilizing the methylphenylsulfoximino moiety as a readily removable directing group.